Large-eddy simulation of the optimal street-tree layout for pedestrian-level aerosol particle concentrations – A case study from a city-boulevard. (April 2020) - Karttunen, Sasu; Kurppa, Mona; Auvinen, Mikko; Hellsten, Antti; Järvi, Leena
Abstract: Street vegetation has been found to have both positive and negative impacts on pedestrian-level air quality, but the net effect has remained unclear. In this study, the effect of street trees on aerosol mass (PM10 and PM2.5 ) and number in a boulevard-type street canyon with high traffic volumes in Helsinki is examined using the large-eddy simulation model PALM. Including a detailed aerosol module and a canopy module to comprise permeable trees, PALM allows to examine the effect of street trees in depth. The main aim is to understand the relative importance of dry deposition and the aerodynamic impact of street trees on the different aerosol measures at pedestrian-level and to find a suitable street-tree layout that would minimise the pedestrian-level aerosol particle concentrations over the boulevard pavements. The layout scenarios were decided together with urban planners who needed science-based knowledge to support the building of new neighbourhoods with boulevard-type streets in Helsinki. Two wind conditions with wind being parallel and perpendicular to the boulevard under neutral atmospheric stratification are examined. Adding street trees to the boulevard increases aerosol particle concentrations on the pavements up to 123%, 72% and 53% for PM10, PM2.5 and total number, respectively. This shows decreased ventilation to be more important for local aerosol particle concentrations than dry deposition on vegetation. This particularly for PM10 and PM2.5 whereas for aerosol number, dominated by small particles, the importance of dry deposition increases. Therefore the studied aerosol measure is important when the effect of vegetation on pedestrian-level air quality is quantified. Crown volume fraction in the street space is one of the main determining factors for elevated mass concentrations on the pavements. The lowest pedestrian-level mass concentrations are seen with three rows of trees of variable height, whereas the lowest number concentrations with four rows of uniform trees. The tree-height variation allows stronger vertical turbulent transport with parallel wind and largest volumetric flow rates with perpendicular wind. Introducing low (height < 1 m) hedges under trees between the traffic lanes and pavements is found to be a less effective mitigation method for particle mass than introducing tree-height variability, and for particle number less effective than maximising the tree volume in the street canyon. The results show how street trees in a boulevard-type street canyon lead to decreased pedestrian-level air quality with the effect being particularly strong for larger aerosol particles. However, with careful planning of the street vegetation, significant reductions in pedestrian-level aerosol particle concentrations can be obtained. Highlights: Street trees weaken pollutant dispersion but also enhance removal by dry deposition. Aerosol dispersion and size-specific dry deposition are studied within urban LES. Generally street trees increase street-level PM10 by 123% and number by 52%. The relative importance of these processes depends on the aerosol size. Variation in street-tree height promotes TKE and turbulent pollutant transport.